2021
DOI: 10.1029/2020jc016714
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Physical and Biogeochemical Variability of the Central Red Sea During Winter

Abstract: The Red Sea is a long, narrow basin spanning a distance of nearly 2,000 km from the strait of Bab al Mandab in the south to the southern tip of the Sinai peninsula in the north. Surrounded by hot deserts, its primary linkage to the global ocean is through the constricted strait of Bab el Mandeb, connecting it to the Arabian Sea through the Gulf of Aden. The Red Sea is characterized by negligible freshwater input from rainfall and terrestrial runoff, high temperatures and high salinity due to solar heating, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Moreover, the bio‐regions were distributed along a latitudinal gradient with, sometimes, the coexistence of several bio‐regions at the same latitude (Figure 1). Such spatial distribution suggests that phytoplankton dynamics might be related to the basin circulation dynamic and/or the availability in nutrients (Eladawy et al., 2017; Gittings et al., 2018; Papadopoulos et al., 2013, 2015; Racault et al., 2015; Raitsos et al., 2013; Zarokanellos and Jones, 2021). Moreover, the phytoplankton phenology (i.e., timing and intensity of phytoplankton bloom) was significantly different between these bio‐regions (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the bio‐regions were distributed along a latitudinal gradient with, sometimes, the coexistence of several bio‐regions at the same latitude (Figure 1). Such spatial distribution suggests that phytoplankton dynamics might be related to the basin circulation dynamic and/or the availability in nutrients (Eladawy et al., 2017; Gittings et al., 2018; Papadopoulos et al., 2013, 2015; Racault et al., 2015; Raitsos et al., 2013; Zarokanellos and Jones, 2021). Moreover, the phytoplankton phenology (i.e., timing and intensity of phytoplankton bloom) was significantly different between these bio‐regions (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…(2018) showed that the position and the intensity of this convergence zone (18°–25°N) vary inter‐annually due to the ENSO influence. Furthermore, note that the observed winter bloom in this region could also result from vertical mixing that dispersed phytoplankton from the deep CHL maximum (Zarokanellos & Jones, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obvious unrealistic spikes in the physical and biogeochemical data were removed manually and replaced by an absent data value (e.g., NaN). Negative values and the dark instrument signal were removed from the chlorophyll fluorescence profiles (Zarokanellos & Jones, 2021). Chlorophyll fluorescence quenching appears mostly near the surface, and can influence fluorescence below the upper few meters, mainly in waters with a low downwelling irradiance attenuation coefficient, Kd, such as the western Mediterranean Sea.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“… Chlorophyll concentrations in the Red Sea observed using (a) the Moderate Resolution Imaging Spectroradiometer (MODIS‐Aqua) on 7 February 2015, revised from Zarokanellos and Jones (2021), (b) MODIS‐Aqua on 29 March 2010, revised from Raitsos et al. (2017), (c) Sea‐viewing Wide Field‐of‐View Sensor (SeaWiFS) on 16 March 2000, revised from NASA earth observatory (https://earthobservatory.nasa.gov/images/8039/chlorophyll%10and%10currents%10in%10the%10red%10sea).…”
Section: Introductionmentioning
confidence: 99%